2019
DOI: 10.1186/s40543-019-0188-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fatty acids in groomed fingerprint by gas chromatographic analysis using various extraction solvents and treatment methods

Abstract: Extremely small amounts of fatty acids detected in latent fingerprints are important for studying fingerprint visualization and age determination through changes in composition over time. However, methods for efficiently extracting or recovering fatty acids from fingerprints have not been extensively studied. If accurate and stable quantitative estimations are established, age estimates will be possible through a better understanding of the fatty acid composition. The extraction solvent and treatment method ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…On average, squalene was the most abundant lipid both in natural and groomed fingermarks, followed by palmitic acid and cholesterol. Similar results have been observed for groomed residue in previous studies [5,9,20,23,25,29,66]. These three compounds are found in the sebum through body synthesis and food consumption [27,28,32,46,47,52,60,67].…”
Section: Lipid Relative Quantities In Natural and Groomed Fingermarkssupporting
confidence: 89%
See 1 more Smart Citation
“…On average, squalene was the most abundant lipid both in natural and groomed fingermarks, followed by palmitic acid and cholesterol. Similar results have been observed for groomed residue in previous studies [5,9,20,23,25,29,66]. These three compounds are found in the sebum through body synthesis and food consumption [27,28,32,46,47,52,60,67].…”
Section: Lipid Relative Quantities In Natural and Groomed Fingermarkssupporting
confidence: 89%
“…Several studies have already focused on the lipid composition of fingermarks [20][21][22][23][24], mainly using gas chromatography (GC) and liquid chromatography (LC) coupled to mass spectrometry (MS), but also other mass spectrometric methods [5,23,[25][26][27][28][29][30][31][32]. As lipids are secreted by the sebaceous glands, most studies were carried out using groomed fingermarks (i.e., marks obtained by rubbing the fingertips on the donor's face or neck to enrich the fingertips in sebum).…”
Section: Introductionmentioning
confidence: 99%
“…The substrate has been shown to affect the amount of material deposited (Weyermann et al, 2011). The method of fingermark extraction and sample preparation can also affect the quantitative data collected for different constituents (Kim et al, 2019).…”
Section: Fingermark Chemistrymentioning
confidence: 99%
“…Many latent fingerprint studies employ random and collective grooming techniques in which participants touch multiple regions of the face prior to depositing fingerprints. ,,, Studies have shown that grooming latent fingerprints is important for the enhancement of low-abundance analytes; , however, some studies suggest sebum concentration may vary by the anatomical location ,, in which the participants groom. If the grooming location affects the lipid profile of latent fingerprints, it is possible this collection step is introducing unnecessary and avoidable variability among samples.…”
Section: Resultsmentioning
confidence: 99%